Prevalence of apical periodontitis and non-retention of root-filled teeth in hypertensive patients: Systematic review and meta-analysis - Cabanillas-Balsera, Daniel; Areal-Quecuty, Victoria; Cantiga-Silva, Cristiane [UNESP]; Cardoso, Carolina de Barros Morais [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Martín-González, Jenifer; Segura-Egea, Juan J. (Wiley, 2024)
Background: Several studies have suggested a relationship between AP, as well as the loss of root-filled teeth (RFT), and hypertension (HTN). Objectives: The aims of this systematic review and meta-analysis were to investigate the prevalence of AP, and non-retention of RFT, in hypertensive patients. Methods: A search was performed in PubMed/MEDLINE, Web of Science, Scopus and EMBASE. The inclusion criteria established were studies published until February 2023, comparing hypertensive subjects with controls, assessing the prevalence of AP and/or providing data on the prevalence of non-retained RFT. Meta-analysis was performed using the RevMan (analyst) tool to determine the pooled prevalence of AP and loss of RFT. Risk of bias was assessed using the Cochrane Risk-of-Bias tool. The quality of evidence was assessed by GRADE. Results: The search strategy identified 454 articles, and only eight met the inclusion criteria. Six studies had analysed the association between AP and HTN and two studies had analysed the association between non-retention of RFT and HTN. Meta-analysis showed and overall OR = 1.71 (95% CI = 0.92–3.16; p =.09) for the prevalence of AP among patients with HTN. The prevalence of non-retention of RFT among patients with HTN has an overall OR = 1.78 (95% CI = 1.60–1.98; p =.000001). The risk of bias in the individual studies was low or moderate, and the quality of the overall evidence has shown a level of certainty very low. Discussion: There is no association between the prevalence of AP and HTN. In addition, hypertensive patients have significantly increased odds of losing RFT. Given the high prevalence of hypertension, it is very common to perform root canal treatments on hypertensive patients. It is imperative to communicate this heightened risk to patients and recommend periodic monitoring of oral health and hypertension, paying special attention to this subset of patients. Registration: PROSPERO CRD42022302385.
Keywords: apical periodontitis; endodontic medicine; hypertension; root canal treatment